Fast-growing painful leg ulcers in a 26-year-old woman with systemic lupus erythematosus: a quiz - Hartmann, Julia; Hänßle, Holger; Enk, Alexander; Toberer, Ferdinand (Acta dermato-venereologica, 2019)
Abstract is missing (Quiz)...
Gesehen am 27.03.2019